Justifying Public Decisions in Arctic Oil and Gas Development: American and Russian Approaches - Flanders, Nicholas E; Brown, Rex V; Andre'eva, Yelena; Larichev, Oleg (ARCTIC, 1998)
Government resource decisions in the Arctic typically involve complex issues; multiple criteria are used to choose among alternatives. This complexity is even greater with petroleum development because of concerns about national energy security, environmental impacts, and economic development. Two decision-aiding techniques may help decision makers clarify their decisions to themselves, the stakeholders, and the general public. The Russian qualitative technique seeks to reduce the number of criteria and find alternative options that may be better than the initial ones. The Western quantitative technique seeks to measure the decision maker* s judgement about the utility and certainty of each option. These techniques are applied to two case studies: a decision about gas pipeline routing on the Yamal Peninsula, Russia, and a tool for evaluating applications for development permits on the North Slope of Alaska. The qualitative method is easier to use and may be the best model for people who use numbers infrequently or want to make a claim based on rights. The quantitative method did well at preserving detail and incorporating uncertainty. Both approaches helped to reduce the apparent complexity of the decisions.